2013
DOI: 10.1155/2013/861460
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Pluripotency and Oocyte-Related Genes in Single Putative Stem Cells from Human Adult Ovarian Surface Epithelium CulturedIn Vitroin the Presence of Follicular Fluid

Abstract: The aim of this study was to trigger the expression of genes related to oocytes in putative ovarian stem cells scraped from the ovarian surface epithelium of women with premature ovarian failure and cultured in vitro in the presence of follicular fluid, rich in substances for oocyte growth and maturation. Ovarian surface epithelium was scraped and cell cultures were set up by scrapings in five women with nonfunctional ovaries and with no naturally present mature follicles or oocytes. In the presence of donated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 43 publications
5
35
0
Order By: Relevance
“…Oocytes from OE patients and healthy donors had similar percentages of reads mapping in unique or multiple locations and number of genes detected at different expression levels (Supplementary Figure S1A, S1B). As a biological control test, we selected 10 genes typically expressed in oocytes (DAZL, KIT, BMP15, ZP1, ZP2 (Virant-Klun et al, 2013) and analysed FPKMs of these genes in the 32 single-cell oocyte libraries. Results demonstrated that FPKMs of these genes were similar between oocytes from healthy donors versus oocytes from the affected or unaffected ovary of endometriosis patients (Supplementary Figure S1C).…”
Section: Global Transcriptome Behaviour In Oocytes From Oementioning
confidence: 99%
“…Oocytes from OE patients and healthy donors had similar percentages of reads mapping in unique or multiple locations and number of genes detected at different expression levels (Supplementary Figure S1A, S1B). As a biological control test, we selected 10 genes typically expressed in oocytes (DAZL, KIT, BMP15, ZP1, ZP2 (Virant-Klun et al, 2013) and analysed FPKMs of these genes in the 32 single-cell oocyte libraries. Results demonstrated that FPKMs of these genes were similar between oocytes from healthy donors versus oocytes from the affected or unaffected ovary of endometriosis patients (Supplementary Figure S1C).…”
Section: Global Transcriptome Behaviour In Oocytes From Oementioning
confidence: 99%
“…The best-characterized VSELs at the molecular level using microarray analysis are murine BM-derived VSELs [23,26,28] and small SSEA-4 + cells corresponding to murine VSELs isolated from human gonads [14,29,30]. Therefore, more work is needed to characterize molecular signature of VSELs isolated from other murine organs (eg, brain, heart, and skeletal muscles) and, in particular, the phenotypically corresponding populations of human VSELs in BM, UCB, and mPB.…”
Section: Introductionmentioning
confidence: 99%
“…. Expression profiles of trophoectoderm markers, inner cell mass markers and stemness markers have also been measured on human single blastomeres from 5 to 8-cell embryos by Galan et al, using microarray4 and in single putative stem cells from human adult ovarian surface epithelium5.…”
mentioning
confidence: 99%